Baltasar Isaza Calderón, La doctrina gramatical de Bello. Imprenta Nacional, Panamá, 1960; 309 pp. - S. Merrill, Judith (El Colegio de México, 1962)
Se reseñó el libro: La doctrina gramatical de Bello.